Intra-rater Reliability and the Role of Experience: A Comparative Case - Isabel Cristina Bolaños Villalobos; Gabriela Cerdas Ramírez; Jimmy Ramírez Acosta (Revista de Lenguas Modernas, 2014)
This article aims to present the results of an investigation which seeks to determine whether experience plays an important role in increasing intra-rater reliability. The paper also provides an analysis that is carried out to determine if factors such as gender or rubric development affect raters’ reliability. Finally, a list of practical implications drawn from this investigation is provided.